Lone Texan - Thomas, Jodi (New York : Berkley Books, 2009)
"Three days after arriving in Galveston, newly widowed Sage McMurray is furious. She's been gone from Texas long enough to forget what it takes to survive on the frontier, and finds herself taken hostage in a robbery. Sage fears if the outlaws discover who she is, she may never see Whispering Mountain again. Her fears are about to come true when the outlaws decide to auction off their pretty captive to the highest bidder, and a tall stranger offers twice the highest bid. Drummond Roak has grown up in the years since Sage left. He now makes his living as a gunfighter, but his love for her has never changed. While fighting to keep her alive, he is also determined to convince the Texas beauty that beneath his wild ways is a man worth loving..."--p. [4] of cover.
98844
Keywords: Widows; Man-woman relationships; Texas; Love stories; Historical fiction